Orthodox Γ-semigroups - M. K. Sen; N. K. Saha (International Journal of Mathematics and Mathematical Sciences)
Let M={a,b,c,…} and Γ={α,β,γ,…} be two non-empty sets. M is called a Γ-semigroup if aαb∈M, for α∈Γ and b∈M and (aαb)βc=aα(bβc), for all a,b,c∈M and for all α,β∈Γ. A semigroup can be considered as a Γ-semigroup. In this paper we introduce orthodox Γ-semigroups and extend different results of orthodox semigroups to orthodox Γ-semigroups.